Neighborhood walkability and risk of gestational diabetes. Issue 1 (20th February 2020) - Kew, Simone; Ye, Chang; Mehmood, Sadia; Hanley, Anthony J; Sermer, Mathew; Zinman, Bernard; Retnakaran, Ravi
Abstract : Objective: Higher neighborhood walkability has been associated with a lower risk of type 2 diabetes mellitus (T2DM) by promoting greater physical activity (thereby reducing weight and lowering insulin resistance). However, it is not known if walkability may similarly reduce maternal risk of gestational diabetes mellitus (GDM), which arises in the setting of the severe physiologic insulin resistance of pregnancy. Indeed, the insulin resistance of pregnancy is primarily driven by placental hormones and not maternal weight gain. Thus, we sought to evaluate the impact of neighborhood walkability on maternal risk of GDM and the pathophysiologic determinants thereof (insulin sensitivity and pancreatic beta-cell function). Methods: In this study, 1318 women reported their pregravid physical activity (Baecke questionnaire) while undergoing an oral glucose tolerance test (OGTT) at mean 29.3 weeks' gestation. The OGTT identified 290 women with GDM and enabled assessment of insulin sensitivity and beta-cell function. Based on their residential Walk Score, the women were stratified into the following four established categories of neighborhood walkability: car dependent (n=328), somewhat walkable (n=315), very walkable (n=406), and walker's paradise (n=269). Results: There was a progressive increase in pregravid total physical activity (p=0.002), non-sport leisure-time activity (p=0.009) and sport activity (p=0.01) across the walkability groups (from car dependent to somewhat walkable to very walkable to walker's paradise), coupled with a concomitant decline in pre-pregnancy body mass index (p=0.007). However, in pregnancy, the groups did not differ in gestational weight gain (p=0.80). Moreover, the walkability groups also did not differ in mean adjusted insulin sensitivity, beta-cell function, or glycemia on the antepartum OGTT. On logistic regression analysis, Walk Score did not predict GDM (OR=1.001, 95% CI 0.995 to 1.007). Conclusion: Neighborhood walkability is not a significant determinant of maternal risk of GDM. Thus, in contrast to T2DM, the effect of neighborhood design on incidence of GDM will be comparatively modest.